ELEMENTS OF AN URBAN TREE RISK MANAGEMENT PROGRAM - Duntemann, Mark (Revista da Sociedade Brasileira de Arborização Urbana, 2006)
The development of effective hazard trees assessment practices has been an important focus of urban forestry for many years. When a publicly owned tree fails and causes property damage, personal injury or death in the United States, a potential consequence for a government agency is litigation. Although managing a large public tree resource can seem daunting, simple assessment parameters can be used to identify high-risk features within the tree population. Through analysis of the interaction between high-risk elements in the tree population and definition of a long-term, managed approach to tree risk reduction, strong policies and practices can be initiated. This program emphasizes two concepts. First, implementation of a well thought out risk reduction strategy improves the overall health of the urban forest, which results in a safer urban environment. This goal is universal, regardless of national boundaries. Second, documentation and implementation of tree risk management policies forms the foundation for a government agency’s defense, if litigation ever occurred.